2015
DOI: 10.1177/2158244015574936
|View full text |Cite
|
Sign up to set email alerts
|

Online Support Groups for Depression

Abstract: This mixed-methods study aimed to explore the initial process of engagement with an online support group (OSG) for depression. Fifteen British National Health Service patients experiencing depression who had not previously used an OSG for depression were offered facilitated access to an existing peer-to-peer OSG for 10 weeks. Pre- and post-measures of depression, social support, and self-stigma were taken in addition to a weekly measure of OSG usage. A follow-up qualitative interview was conducted with a subsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
3
23
1
Order By: Relevance
“…This study highlights some of the positive functions of blog writing, but negative aspects of online communication, such as social isolation and trolling also exist (Finn and Lavitt, 1994;Breuer and Barker, 2015). However, the relative newness of using blogging within academic research (Hookway, 2008) and the tendency for research to focus upon children's online behaviour and experiences (see for example Mitchell, Wolok and Finkelhor, 2008) means research on the potential negative experiences of blogging amongst adult sexual assault victims is currently unknown.…”
Section: Implications and Future Researchmentioning
confidence: 90%
“…This study highlights some of the positive functions of blog writing, but negative aspects of online communication, such as social isolation and trolling also exist (Finn and Lavitt, 1994;Breuer and Barker, 2015). However, the relative newness of using blogging within academic research (Hookway, 2008) and the tendency for research to focus upon children's online behaviour and experiences (see for example Mitchell, Wolok and Finkelhor, 2008) means research on the potential negative experiences of blogging amongst adult sexual assault victims is currently unknown.…”
Section: Implications and Future Researchmentioning
confidence: 90%
“…This may be that connecting with others online is not as confrontational and gives the user more control of the interaction when compared to face-to-face meetings (Breuer, & Barker, 2015;Evans, Donelle, & Hume-Loveland, 2012). Fitting with past research on health related social media use, it was younger and middle aged females who suggested social support features (Thackeray, Crookston, & West, 2013).…”
Section: Web-based Physical Activity Intervention Preferencesmentioning
confidence: 99%
“…Horgan, McCarthy, and Sweeney (2013) found indication that an online environment allows users to receive emotional and social support through identifying with others experiencing the same symptoms. Breuer and Barker (2015) report mixed findings, with participants describing a reduction in depressive symptomology over a ten-week period alongside concern over harming others or themselves because of OF interaction. Whilst further investigation is needed to determine whether OF environments reduce symptoms (Griffiths et al, 2012;Melling & Houguet-Pincham, 2011), access to appropriate networks for health discussion has been found to be important for illness recovery (Perry & Pescosolido, 2015), and so seeking social support may be viewed as a form of help-seeking behaviour.…”
Section: Introductionmentioning
confidence: 96%
“…The ambivalence expressed by some participants regarding socialisation could be explained within this context, in that belonging to a virtual group with like-minded others is more attractive than real-life interaction. The anonymity afforded by OF environments enables personal information to be confidentially shared (Breuer & Barker, 2015), and may also allow individuals to mediate any stigma or self-stigma that may act as a barrier to accessing other forms of care (Wang et al, 2015).…”
Section: The Negative Selfmentioning
confidence: 99%
See 1 more Smart Citation